Development of Flipbook-Based Digital Comic Media to Improve Student Learning Outcomes in Indonesian Language Learning - Siti Nur Lailatul Nikmah; Nino Indrianto (Progressive Journal of Educational Science, 2025)
This study aims to produce a product, the feasibility of development and effectiveness of Flipbook-based Digital Comic media to improve student learning outcomes in Indonesian language learning in class IV MI NU Nurul Fattah Puger Jember. This research method uses research and development with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of this study were assessment questionnaires conducted by expert validators (media, material and language) using validation questionnaires, and user expert questionnaires (class teachers) and student response questionnaires to flipbook-based digital comic media. Based on the results of the study, it can be concluded that Digital Comic Media is a learning media that can actually be created and developed by everyone. Because this Digital Comic media is made using the Canva application. The results of the media validation got a score of 92.5% and the results of the material expert validation got a score of 90%. The results of the learning expert validation got a score of 96%. The results of the expert validation and also the response got an average score of 92.5% with a very valid category or said to be feasible, because the score results obtained had an average of 90% and above. From the results of the analysis, it can be concluded that Flipbook-based Digital Comic Media is very feasible and effective in helping teachers and students to deliver Mathematics learning.